Effect of row spacing and herbicide programs for control of glyphosate-resistant Palmer amaranth (Amaranthus palmeri) in dicamba/glyphosate-resistant soybean. (11th October 2021) - McDonald, Shawn T.; Striegel, Adam; Chahal, Parminder S.; Jha, Prashant; Rees, Jennifer M.; Proctor, Christopher A.; Jhala, Amit J.
Abstract: Glyphosate-resistant (GR) Palmer amaranth is one of the most difficult to control weeds in soybean production fields in Nebraska and the United States. An integrated approach is required for effective management of GR Palmer amaranth. Cultural practices such as narrow row spacing might augment herbicide efficacy for management of GR Palmer amaranth. The objectives of this study were to evaluate the effect of row spacing and herbicide programs for management of GR Palmer amaranth in dicamba/glyphosate-resistant (DGR) soybean. Field experiments were conducted in a grower's field with a uniform population of GR Palmer amaranth near Carleton, Nebraska, in 2018 and 2019. Year-by-herbicide program-by-row spacing interactions were significant for all variables; therefore, data were analyzed by year. Herbicides applied PRE controlled GR Palmer amaranth ≥95% in both years 14 d after PRE (DAPRE). Across soybean row-spacing, most PRE followed by (fb) early-POST (EPOST) herbicide programs provided 84% to 97% control of Palmer amaranth compared with most EPOST fb late-post (LPOST) programs, excluding dicamba in single and sequential applications (82% to 95% control). Mixing microencapsulated acetochlor with a POST herbicide in PRE fb EPOST herbicide programs controlled Palmer amaranth ≥93% 14 d after EPOST and ≥96% 21 d after LPOST with no effect on Palmer amaranth density. Interaction of herbicide program-by-row spacing on Palmer amaranth control was not significant; however, biomass reduction was significant at soybean harvest in 2019. The herbicide programs evaluated in this study caused no soybean injury. Due to drought conditions during a majority of the 2018 growing season, soybean yield in 2018 was reduced compared with 2019.